The Effect of Palm Oil Fly Ash Reinforcement on Recycle Aluminium via Sand Casting - Hafiz Mohd Noh, Mohd; Ismail, Azzura; Hussein Abdul Hamid, Ahmad (International Journal of Engineering and Technology, 2018)
Recycle aluminium has been mixed with palm oil fly ash based on fraction weight of overall weight of palm oil fly ashes to aluminium recycle. The ratios discussed on this paper are 0%, 3% 6%, 9%, 12% and 15%. The samples have been developed via sand casting method. The result shows that the best composition has been achieved when we added 3% of palm oil fly ashes, with the new composite aluminum have a highest hardness with the value of 119.7HV, with the Modulus of raptured of 7.71Mkg/m2Â Â